This preview shows page 1. Sign up to view the full content.
Unformatted text preview: of zero. Next, in order to move the exponent down it has to be on the whole term
inside the logarithm and that just won’t be the case with this equation in its present form.
So, the first step is to move on of the terms to the other side of the equal sign, then we will take
the logarithm of both sides using the natural logarithm. 2 4 y +1 = 3 y
ln 2 4 y +1 = ln 3 y ( 4 y + 1) ln 2 = y ln 3
Okay, this looks messy, but again, it’s really not that bad. Let’s look at the following equation
first. 2 ( 4 y + 1) = 3 y 8y + 2 = 3y
5 y = -2
We can all solve this equation and so that means that we can solve the one that we’ve got. Again
the ln2 and ln3 are just numbers and so the process is exactly the same. The answer will be
messier than this equation, but the process is identical. Here is the work for this one. ( 4 y + 1) ln 2 = y ln 3 4 y ln 2 + ln 2 = y ln 3
4 y ln 2 - y ln 3 = - ln 2
y ( 4 ln 2 - ln 3) = - ln 2
y=- ln 2
4 ln 2 - ln 3 So, we get all the terms with y in them on one side and a...
View Full Document
This note was uploaded on 06/06/2012 for the course ICT 4 taught by Professor Mrvinh during the Spring '12 term at Hanoi University of Technology.
- Spring '12